Mechanical characterisation and machining evaluation of ceramic cutting tools functionally graded with six layers. Issue 10 (July 2020) - Bertolete, M.; Barbosa, P.A.; de Rossi, W.; Fredericci, C.; Machado, I.F.
Abstract: Functionally graded materials (FGMs) are composites graded in one or more directions by the mean volume fraction variation of their constituents in a continuous or stepwise design. The objective of this study is to apply the FGM concept to ceramic cutting tools to widen its application range. Thus, two cutting tool materials were selected: cemented carbide, owing to its higher toughness, and alumina-based ceramic, owing to its high wear resistance at elevated temperatures. Ceramics based on alumina were functionally graded with cemented carbide and sintered using the spark plasma sintering technique. The thermal residual stresses were predicted; additionally, the microstructure, relative density, and Vickers hardness and fracture toughness for the alumina layer were evaluated, and flexural strength and machining tests were conducted. From the results, cracks were not observed in the microstructure and full density was obtained. In general, the hardness and fracture toughness values were close to those in the literature. A flexural strength improvement of at least 50% on FGM samples was observed in comparison to homogeneous ceramic ones. The FGM cutting tools supported approximately 1000 N of machining force without catastrophic failure when turning martensitic stainless steel into a conventional lathe. The values of surface roughness (Ra and Rz) agree with those in the literature under similar cutting and geometry conditions.